WHEN LEARNING MEDIA PLAYS ROLES IN TEFL: HOME-VISITING STUDY CASE DURING COVID 19 (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
This study describes the implementation of learning media during the program of “home visit”. The activity involved 15 students of 6th grade of MI Unwaanul Falah, South Tangerang, as the subjects of the research. A qualitative-descriptive method was applied in this study. The researchers collected the data through observation, students’ assignment results and documentary pictures. The techniques in analyzing the data included data reduction, data display, and also conclusion and verification.  The results of the research showed that the students responded to lessons better when the learning process was carried out in an interesting and interactive way, such as the used of diverse and concrete learning media which created enjoyable and appealing learning process during the COVID-19 pandemic.